2015
DOI: 10.1021/acs.jpcc.5b05722
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ab Initio Molecular Dynamics Simulation of the Temperature-Dependent Thermodynamics for the Diffusion of Carbon Monoxide on Ru(0001) Surface

Abstract: CO diffusion on the metal surface is an elementary process in many heterogeneous catalytic reactions. The thermodynamics and the molecular mechanism of the diffusion process are key factors contributing to the kinetics of the catalysis. Theoretical study based on computer simulations can complement experimental studies to provide much needed thermodynamic and mechanistic information. Here, we report direct ab initio molecular dynamics (MD) simulation to investigate the temperature-dependent thermodynamics of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
2
6
0
Order By: Relevance
“…Our results unexpectedly showed that the relative free energy between top and hcp sites increases rather than reduces as the temperature raising, being contrary to the intuition (see Figure 2). The PMF surfaces in Figure 1 and S5 obviously suggest that the free energy curve in top site is flatter than that in hcp site, in agreement with our previous results that the frequency of the two in-plane modes is lower in the top site, 35 and further suggests the top site has less steric interactions.…”
Section: Discussionsupporting
confidence: 89%
“…Our results unexpectedly showed that the relative free energy between top and hcp sites increases rather than reduces as the temperature raising, being contrary to the intuition (see Figure 2). The PMF surfaces in Figure 1 and S5 obviously suggest that the free energy curve in top site is flatter than that in hcp site, in agreement with our previous results that the frequency of the two in-plane modes is lower in the top site, 35 and further suggests the top site has less steric interactions.…”
Section: Discussionsupporting
confidence: 89%
“…Free of reaction coordinates (RCs) facilitates ITS be applicable to complex processes with rugged energy landscape such as protein folding. Very recently, the applicability of ITS method has been further extended to some heterogeneous catalytic systems [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it was shown to be a suitable approach for low-energy activated processes such as carbene decomposition on a Ni(111) surface 244 or CO diffusion on a Ru(0001) surface. 243 …”
Section: Free Energy Techniquesmentioning
confidence: 99%